Factors Affecting the Weaving Wisdom Management of the Weaving Group Members in Luang Prabang Province, Lao People’s Democratic Republic - Phaignavon, Somchay; Fongmul, Saisakul; Sakkatat, Phahol; Kanokhong, Kangsadan (Community and Social Development Journal, 2024)
The purpose of this research was to study basic personal, social, economic and factors related to weaving wisdom management of members of Luang Prabang Weaving Group. Lao People's Democratic Republic By collecting data from members of the weaving group of Luang Prabang Province, Lao PDR; The data was collected by the questionnaires from 326 samples of weaving group in 15 villages The sample group were sampled using a computational method and using descriptive statistics to analyze frequency, percentage, mean, and standard deviation and conducting Enter Multiple Regression Analysis The findings of this study revealed that sampling average age group are 50.12 years old; 82.8 percent of sampling group are weaving as their major job; 85 percent are registered as weaving group members; and had 29.35 years of experience, the annual family income from weaving activities totaling around 20,279 Thai Baths (THB) and the factors related to knowledge management of weaving wisdom among weaving group members in Luang Prabang Province Lao People's Democratic Republic. It was found that all 15 independent variables had 47.50 percent (R2 =0.475) of weaving wisdom knowledge management of the members of the weaving group in LuangPrabang Province. The remaining 52.50 percent were influential from other factors not determined in this study. and when considering the independent variables affecting knowledge management of weaving wisdom in Luang Prabang province. statistically significant It was found that there were altogether 3 variables, with 2 positive effects, namely the position in the village. Receiving information about weaving and negatively affecting one variable, experience about weaving. which has a statistically significant correlation at the 0.05 level.